Empires of Vision : A Reader - Ramaswamy, Sumathi; Jay, Martin, 1944- (Book collections on Project MUSE., 2014)
Combining visual culture and postcolonial studies, this reader shows that an appreciation of the role of visual experience is necessary for understanding how colonialism worked and how colonized subjects spoke to imperial rulers.